Radiotherapy as a primary treatment modality for a young man with a primary urethral plasmacytoma: case report and literature review - Lim, Soo How; Poh, Tian Er; Wee, Hong Chin; Awang Basry, Nur Shazwaniza Binti; Tajul Arifin, Mohd Syazwan Bin; Yong, Kar Ying (Frontiers in Oncology, 2025)
Primary urethral plasmacytoma is an extremely rare form of solitary plasmacytoma, with only 10 cases reported in the literature. It involves localized clonal proliferation of plasma cells without systemic disease. This report presents a 29-year-old man with acute urinary retention and a urethral mass, confirmed as solitary plasmacytoma. The patient was treated with 45 Gy of local radiotherapy, resulting in complete tumor resolution without recurrence or progression at a 2-year follow-up. Given its rarity, treatment strategies for primary urethral plasmacytoma are not well-defined. Radiotherapy is preferred over surgery in young patients due to the radiosensitivity of plasma cell tumors and its ability to preserve sexual and urinary function. A review of previous cases treated with radiotherapy alone, using doses of 40–50 Gy, showed favorable outcomes with no recurrences reported over follow-up periods ranging from 6 months to 12 years. Only one patient experienced minor long-term complications. This report highlights the effectiveness of radiotherapy as a primary modality for managing primary urethral plasmacytoma, offering excellent local control while preserving organ function. Individualized treatment plans should consider patient age, fertility concerns, and tumor characteristics. Further research is necessary to optimize treatment protocols and long-term surveillance strategies due to the potential risk of recurrence or progression to multiple myeloma.